Accident at School. Civil Law Dimension of School – Teacher – Student Relations - Tomkiewicz, Małgorzata (Studia Warmińskie, 2014)
The article concerns the accident issue at school analysed in terms of civil liability. It contains a synthetic analysis of educational law, civil law, and labour law regulations relating to the responsibility of the three major parties: the school (the body responsible for the school), the teacher and the student. It is an attempt to answer the question of who, when, and to what extent and on what basis the party shall be financially liable for damages arising from an accident at school.